Market Concentration, Capital and Risk Taking in Banking Industry - Erika Sefila Putri; Rahmat Setiawan (Jurnal Manajemen Teori dan Terapan | Journal of Theory and Applied Management, 2021)
Banking market concentration is an interesting banking topic to study because the banking market structure plays an important role in a country's banking system. This study aims to determine the relationship between banking market concentration and bank risk taking, and bank capital as a moderating variable on the relationship between bank capital and bank risk taking. The test was conducted using multiple linear regression on 104 conventional commercial banks in Indonesia from 2007 to 2016. The results of this study indicate that banking market concentration has a positive effect on bank risk-taking, and bank capital weakens the positive effect of bank market concentration on bank risk-taking.